Parenting style and the non-cognitive development of high school student: evidence from rural China - Wang, Sangui; Zheng, Lijuan (Frontiers in Psychology, 2024)
In order to understand the relationship between parenting style and the non-cognitive development of high school students in rural China, this study surveyed 6,549 high school students and their primary caregivers. The students have an average age of 17.61 years (48% were male), and 62% were of Han ethnicity. Primary caregivers self-reported their parenting style, and students' non-cognitive abilities were evaluated using the Big Five Inventory-Short (BFI-S). The relationship between parenting style and students' non-cognitive development was analyzed using two distinct methods (two dimensions and four categories). The study revealed that an authoritative parenting style had a positive impact on the non-cognitive abilities of students. Conversely, a negative association was observed between the authoritarian parenting style and the non-cognitive development of students. The association between the authoritative and authoritarian styles is more pronounced in relation to the non-cognitive developmental score of girls compared to boys. Additionally, parents from a wealthier family or with higher levels of education were more likely to use an authoritative rather than an authoritarian parenting style. The results of this study provide impetus for further investigation into the implementation of parenting training interventions aimed at assessing the potential efficacy of cultivating an authoritative parenting style among rural Chinese parents.